Progressive damage mechanism of rock-anchoring interface under cyclic impact loading - Peng Wang; Nong Zhang; Jiaguang Kan; Zhengzheng Xie; Guangzhen Cui; Feng Guo; Chuang Cao; Zhe Xiang; Changliang Han (Scientific Reports)
Abstract Cyclic impacts induce progressive fatigue damage at the rock–anchoring interface, thereby compromising the stability of deep roadway support systems. In this study, the split Hopkinson pressure bar and low-field nuclear magnetic resonance techniques were employed to investigate the macro- and micro-scale damage evolution mechanisms of the anchoring interface under varying conditions, including rock type, anchorage angle, and impact air pressure. The results demonstrate that with increasing impact air pressure, both the dynamic compressive strength and average strain rate at the anchoring interface increase. Under cyclic impacts at a constant air pressure, the maximum strain and strain rate increase with each successive impact, while the dynamic compressive strength progressively declines. As the number of impacts accumulates, the total volume of internal pores and pore throats expands, accompanied by a substantial rise in the proportion of large-diameter pores. Changes in elastic potential energy dominate the failure process, which follows a characteristic progression: fissure compression, initiation, propagation, penetration, and final rupture. The observed failure modes include crushing, irregular longitudinal splitting, shear-slip cracking along the interface, and debonding failure. These modes are closely related to the substrate rock strength, interface angle, and impact air pressure. A mismatch in compressive strength and deformation incompatibility between materials were identified as key contributors to failure. Therefore, when selecting anchoring materials, both strength and ductility should be considered to enhance their cooperative load-bearing performance.